2006
DOI: 10.4049/jimmunol.177.2.1289
|View full text |Cite
|
Sign up to set email alerts
|

Human Monocytes Recognize Porcine Endothelium via the Interaction of Galectin 3 and α-GAL

Abstract: Monocytes are one of the key inflammatory cells recruited to xenografts and play an important role in delayed xenograft rejection. Previous studies have demonstrated the ability of monocytes to bind to the major xenoantigen Gal-α(1,3)Gal-β(1,4)GlcNAc-R; however, the receptor that mediates this interaction has yet to be identified. We provide evidence that it is Galectin-3, a ∼30-kDa lectin that recognizes β-galactosides (Gal-β(1–3/4)GlcNAc) and plays diverse roles in many physiological and pathological events.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 38 publications
(28 reference statements)
1
41
0
Order By: Relevance
“…Besides Fc␥ and complement receptors, it has been postulated that lectin-mediated carbohydrate binding provides activating signals to macrophages without opsonization (26). A recent study has shown that Galectin-3, an Ϸ30-kDa lectin composed of a terminal carbohydrate recognition domain, which is responsible for the specific recognition of ␤-galactose [Gal␤(1-3/4) GlcNAc] and an N-terminal domain, is expressed in human macrophages (27). This lectin has been shown to be a receptor for xenoantigens, including not only ␣-Gal but also Nglycolylneuraminic acid, which is expressed on porcine cells.…”
Section: Discussionmentioning
confidence: 99%
“…Besides Fc␥ and complement receptors, it has been postulated that lectin-mediated carbohydrate binding provides activating signals to macrophages without opsonization (26). A recent study has shown that Galectin-3, an Ϸ30-kDa lectin composed of a terminal carbohydrate recognition domain, which is responsible for the specific recognition of ␤-galactose [Gal␤(1-3/4) GlcNAc] and an N-terminal domain, is expressed in human macrophages (27). This lectin has been shown to be a receptor for xenoantigens, including not only ␣-Gal but also Nglycolylneuraminic acid, which is expressed on porcine cells.…”
Section: Discussionmentioning
confidence: 99%
“…It is probable that the vigorous rejection of human RBCs by macrophages is accounted for predominantly by the xenoantigens on human RBCs that can activate macrophages. 34,35 Previous studies have shown the presence of human macrophages and dendritic cells in the humanized mice. 12,13,36 However, we do not fully understand why human macrophages did not reject mouse RBCs in these mice.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, these results are consistent the Gal antigen. These ligands are known to participate in the human monocyte-PAEC interactions (19,21). with previous observations in pig arthritic joints in which the majority of chondrocytes expressed high lev-…”
Section: Pcc Secrete Pil-8 and Pil-6 In Response Tomentioning
confidence: 99%